Catheter ablation of electrical storm in patients with structural heart disease - Segeťová, Markéta; Peichl, Petr; Čihák, Robert; Wichterle, Dan; Vančura, Vlastimil; Bytešník, Jan; Kautzner, Josef (Europace, 2011)
AIMS: Electrical storm (ES) adversely affects prognosis of patients and may become a life-threatening event. Catheter ablation (CA) has been proposed for the treatment of ES. Our goal was to evaluate the efficacy of CA ablation both in acute and long-term suppression of ES. METHODS AND RESULTS: Fifty consecutive patients with coronary artery disease (38), idiopathic dilated cardiomyopathy (5), arrhythmogenic right ventricular cardiomyopathy (6), and/or with combined aetiology (1) underwent CA for ES. Mean left ventricular ejection fraction (LVEF) was 29 ± 11%. All patients underwent electroanatomical mapping, and CA was performed to abolish all inducible ventricular arrhythmias. The ES was suppressed by CA in 84% of patients. During the follow-up of 18 ± 16 months, 24 patients had no recurrences of any ventricular tachycardia (VT; 48%). Repeated procedure was necessary to suppress the recurrent ES in 13 cases (26%). Statistical analysis revealed that low LVEF (22 ± 3 vs. 31 ± 12%; P < 0.001), increased LVend-diastolic diameter (72 ± 9.1 vs. 64 ± 8.9 mm; P = 0.0135), and renal insufficiency (P < 0.001) were the univariate predictors of early mortality or necessity for heart transplantation. Recurrence of ES despite previous CA procedure was associated with a higher risk of death or heart transplant during follow-up (P < 0.05). CONCLUSION: Catheter ablation is effective in acute suppression of ES and often represents a life-saving therapy. In the long term, it prevents recurrences of any VT in about half of the treated patients.
Keywords: Follow-Up Studies; retrospektivní studie; srdeční arytmie; fibrilace komor; Comorbidity; nemoci srdce; Kaplan-Meier Estimate; Humans; lidé; Tachycardia, Ventricular; Heart Diseases; Retrospective Studies; následné studie; komorová tachykardie; lidé středního věku; komorbidita; Treatment Outcome; Middle Aged; Coronary Artery Disease; Ventricular Fibrillation; Female; Male; Arrhythmias, Cardiac; dilatační kardiomyopatie; výsledek terapie; mužské pohlaví; Aged; Catheter Ablation; katetrizační ablace; ženské pohlaví; Cardiomyopathy, Dilated; nemoci koronárních tepen; Kaplanův-Meierův odhad; senioři